PERAN MODAL SOSIAL SEBAGAI MODAL PENGEMBANGAN KOPERASI KREDIT KELING KUMANG KABUPATEN SINTANG - Imam Asrori; Venny Adhita Octaviani (Universitas Kapuas Sintang, 2025)
The Purpose of the research was to identify, how the role of social capital was in the development of a credit union of “Keling Kumang” that consisted of the Strategy of the board of the Credit Union in developing a trust, network development, and the establishment of a shared value. The data for the research was collected through interview, observation, as well as documentation. Based on the result of the interviews, it was concluded that social capital has been taken into account in the development process of “Keling Kumang” Credit Union. The element of social capital in the forms of trust, networks and shared value have been fundamental for the Credit Union of “Keling Kumang”. The strategy that have been applied to raise trust was by the implementation of open and transparant management of the credit union; in the process of the networks development, the strategy was by the application of cooperation with institutions, both domestic and foreign ones, and also developing a member enterpreneurs whereas in the development of a shared value, was through education and undergoing some activities of “Keling Kumang” Credit Union which were based on the shared value.The indicators of the development of the Credit Union of „Keling Kumang” were the raising number of members, raising amount of savings, as well as the assets of the Credit Union of „Keling Kumang”.